DigitalHub: A Repository Focused on the Future. Issue 1 (2nd January 2018) - Ilik, Violeta; Hebal, Piotr; Olson, Anton; Wishnetsky, Susan; Pastva, Joelen; Kubilius, Ramune; Shank, Jonathan; Gutzman, Karen; Chung, Margarita; Holmes, Kristi
ABSTRACT: The DigitalHub scholarly repository was developed and launched at the Galter Health Sciences Library for the Feinberg School of Medicine and the greater Northwestern Medicine community. The repository was designed to allow scholars the ability to create, share, and preserve a range of citable digital outputs. This article traces the evolution of DigitalHub's development and engagement activities, highlighting project challenges, innovations, success stories, and the team-based approach that was employed to successfully achieve project goals.